Análise sobre o fenômeno da transposição didática interna no ensino de estatística: um estudo com a inclusão de um aluno cego em uma sala de aula regular - Santos, Vanessa Lays Oliveira dos (2020)
This work approaches the Didactical Transposition phenomenon proposed by Yves Chevallard (1991). In the field of Mathematics Didactics, this phenomenon describes the path covered by knowledge since its creation in the scientific community until it becomes an object of teaching in schools. The discussions were centralized in the Internal Didactic Transposition, which occurs inside the classroom, and the highlighted theoretical directions were based on the researchers: Araújo (2009), Bessa de Menezes (2004, 2010) and Brito Menezes (2006). The concerns that led us to this investigation are related to the high number of students with visual impairment included in regular schools, a reality which requires new methodologies from the teacher, so that he can attend the needs of these students in this current didactic scenario. Based on the perspective of internal didactic transposition, we analyzed the distance between the knowledge effectively taught to a blind student from the knowledge effectively taught to students without visual impairment, during the teaching of statistics, specifically in a class on the measures of central tendency (mean, median and mode), and in the construction and interpretation of graphs and tables. This research was taken as a qualitative basis, where we did a study with a blind student in a 9th grade class at a public school. The methodological development was divided into three stages: i) class observations; ii) semi-structured interviews/informal conversations, and iii) analysis of collected data. At the end of these stages, even with incipient data, we realized a distance from the knowledge effectively taught to both students (blind/non-blind). In addition, we observed that the distance between this knowledge compromises the mathematical background presented to the blind student, which may lead difficulties in the progress of these contents later.